2018
DOI: 10.1002/ijc.31305
|View full text |Cite|
|
Sign up to set email alerts
|

Association between metformin use after surgery for colorectal cancer and oncological outcomes: A nationwide register‐based study

Abstract: Colorectal cancer is one of the most common malignancies in the Western world, and even after surgical removal, there is a high recurrence rate. Metformin treatment has been associated with a reduced risk of developing cancer, but whether metformin influences the risk of recurrence is unknown. The aim of our study was to examine the association between treatment with metformin and recurrence-free, disease-free survival and all-cause mortality after surgery for colorectal cancer. The study was an observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…Metformin, an oral biguanide agent that was FDA-approved in 1957, has been used as a safe and cost-efficient treatment for T2D worldwide (45,46). Numerous studies have indicated that long-term administration of metformin reduces the risk of various types of cancer, including breast, colon and endometrial cancer, and glioma (13-17,20,47). Recently, Li et al (48) demonstrated that metformin can increase the survival rate of diabetic patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin, an oral biguanide agent that was FDA-approved in 1957, has been used as a safe and cost-efficient treatment for T2D worldwide (45,46). Numerous studies have indicated that long-term administration of metformin reduces the risk of various types of cancer, including breast, colon and endometrial cancer, and glioma (13-17,20,47). Recently, Li et al (48) demonstrated that metformin can increase the survival rate of diabetic patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiological studies have suggested that the use of metformin is associated with a decreased incidence of cancer, and improved prognosis and cancer-associated mortality in patients with T2D (13,14). The anticancer effects of metformin have been reported in breast (15,16), colorectal (17), liver (18), cervical (19), endometrial (20), gastric (21), lung (22), ovarian (23), prostate (24), pancreatic (25) and renal (26) cancer. Various studies have demonstrated that the anticancer mechanisms of metformin are mediated via the AMPK/mammalian target of rapamycin (mTOR) cascade, and the signaling is dependent on AMPK activation leading to inhibition of mTOR that represses protein synthesis, cell proliferation, cell cycle progression and apoptotic cell death (27-29).…”
Section: Introductionmentioning
confidence: 99%
“…Although agreement in the literature is not uniform (10,11), a growing evidence base of population-based studies (12)(13)(14)(15)(16)(17) shows reduced cancer (including colorectal cancer; refs. 18,19) incidence and cancer-specific death among diabetics using metformin versus other treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies which attempted to avoid the potential confounders of adjuvant therapy, focused more on stratified patients by TNM stage, did not show any effect of metformin on the course of CRC. Recent prospective studies suggested at least a 15% decrease in risk of all-cause mortality in CRC patients with T2DM treated with metformin compared with patients receiving insulin [[23], [24], [25], [26]].…”
Section: Introductionmentioning
confidence: 99%